2019
DOI: 10.1186/s12879-019-3875-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the complex relationship between women’s sanitation practices and household diarrhea in the slums of Nairobi: a cross-sectional study

Abstract: BackgroundDiarrheal disease kills over half a million people each year in sub-Saharan Africa; the majority are children under 5 years. About 58% of diarrhea cases are associated with poor water, sanitation, and hygiene—a critical issue for people living in informal settlements. In Kenya, 60% of Nairobi’s population lives in informal settlements; yet, there is a paucity of research exploring the relationship between water, sanitation and hygiene (WASH) conditions in these settlements and associated health outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Environmental factors. Research has shown that lack of access to water and sanitation may be associated with poor health outcomes for women in informal settlements [17,23,25,57,58]. Access to water and sanitation are also used as alternative or additional sociodemographic or wealth measures in these settlements [59,60].…”
Section: Methodsmentioning
confidence: 99%
“…Environmental factors. Research has shown that lack of access to water and sanitation may be associated with poor health outcomes for women in informal settlements [17,23,25,57,58]. Access to water and sanitation are also used as alternative or additional sociodemographic or wealth measures in these settlements [59,60].…”
Section: Methodsmentioning
confidence: 99%
“…(8) Slums are characterized by high population density, small informal dwellings, lack of access to clean water, multi-generational households, shared sanitation facilities among multiple households, a high level of both inter-and intra-social mixing within slums and other areas in Nairobi, transient residence, and poor health outcomes related to both poor environmental conditions and inability to pay for medical care. (9)(10)(11)(12)(13) Compared to the rest of Nairobi, slum dwellers have a higher overall mortality rate, (13) higher rates of mobility around Nairobi, (14) and the population is vulnerable to economic shocks, as most residents rely on income from the informal sector. As data suggest a bidirectional relationship between poverty and health exists in these slums, (13) the dual economic and health crises posed by COVID-19 will be particularly dire.…”
Section: Introductionmentioning
confidence: 99%
“…Since girls and women need to use toilets more often for urination and menstrual hygiene, they often suffer an additional cost burden when accessing pay-per-use toilets and latrines in informal settlements, as noted by Kwiringira et al, (2014) in Uganda. Consequently, they may go without drinking and relieving themselves for long periods of time, or use plastic bags and buckets when they cannot access a toilet, putting them and their families at greater risk of illness (Winter et al, 2019). For women and girls with disabilities these burdens are even more severe, due to physical mobility issues, social Girls and women also perform a number of caregiving tasks that carry severe health risks, often exacerbated by the built environment.…”
Section: Important Statisticsmentioning
confidence: 99%